Comparação entre parâmetros externos e internos de ninhos de Atta bisphaerica Forel, 1908 (Hymenoptera, Formicidae) - Moreira, Aldenise Alves [UNESP]; Forti, Luiz Carlos [UNESP]; De Andrade, Ana Paula Protti [UNESP]; Castellani Boaretto, Maria Aparecida; Ramos, Vania Maria [UNESP]; Santos Lopes, Juliane Floriano [UNESP] (My University, 2002)
Six Atta bisphaerica, Forel, 1908 (Hymenoptera, Formicidae) nests were excavated with the aim of studying the relationship between area and volume of the mound, the total volume and total number of chambers in the nest. Prior to excavation, the area and the volume of refused soil in the nests were measured. During excavation, all data referring to chambers were recorded, such as: length, depth and width. The nests named A1, A2, A3, A4, A5 and A6 presented 31.16; 40.87, 67.08, 35.04, 73.48 and 18,73m 2 of mound area, respectively. The mound area did not correlate either with the volume or with the total number of chambers. The mound volume correlated significantly with the mound area, total number and total volume of chambers. The total volume of chambers was correlated with the total number of chambers.
Comparison between external and internal parameters of Atta bisphaerica Forel, 1908 (Hymenoptera, Formicidae) nests
Keywords: Area; Atta bisphaerica; Chambers; Nest; Volume; controlled study; correlation analysis; geometry; Hymenoptera; insect society; nesting; nonhuman; soil; Atta; Formicidae; Insecta